Revision of the Tephritis maccus species group (Diptera: Tephritidae) with description of a new species from Iran - Namin, Saeed Mohamadzade; Korneyev, Severyn V. (Zootaxa, 2015)
The maccus species group of the genus Tephritis Latreille 1804 is revised. The maccus group contains five species with a radiate wing pattern, cell r1 without or with only one large hyaline spot or indentation on the anterior wing margin, and the aculeus moderately broad, sharply narrowing and pointed at the very apex. The included species are: Tephritis azari Mohamadzade Namin & Korneyev, Tephritis gharalii sp. nov., Tephritis maccus Hering, Tephritis sophus and Tephritis urelliosomima Korneyev & Dirlbek.